2005
DOI: 10.1182/blood-2004-08-2988
|View full text |Cite
|
Sign up to set email alerts
|

SATB1 family protein expressed during early erythroid differentiation modifies globin gene expression

Abstract: Special AT-rich binding protein 1 (SATB1) nuclear protein, expressed predominantly in T cells, regulates genes through targeting chromatin remodeling during T-cell maturation. Here we show SATB1 family protein induction during early human adult erythroid progenitor cell differentiation concomitant with ⑀-globin expression. Erythroid differentiation of human erythroleukemia K562 cells by hemin simultaneously increases ␥-globin and down-regulates SATB1 family protein and ⑀-globin gene expression. Chromatin immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(84 citation statements)
references
References 52 publications
3
81
0
Order By: Relevance
“…More recent studies have revealed that SATB1 is involved in the reconstruction of global genomes and regulates the expression of more than 1,000 genes. There is evidence to suggest that SATB1 modulates cell proliferation and lineage development and SATB1 is significant in breast cancer (7,11,12,20). The mechanism by which SATB1 contributes to the malignant phenotypes of tumor cells is poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies have revealed that SATB1 is involved in the reconstruction of global genomes and regulates the expression of more than 1,000 genes. There is evidence to suggest that SATB1 modulates cell proliferation and lineage development and SATB1 is significant in breast cancer (7,11,12,20). The mechanism by which SATB1 contributes to the malignant phenotypes of tumor cells is poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…It is expressed predominantly (but not exclusively: see Wen et al 2005) in thymocytes where it represents one of the few gene products that are induced early upon peripheral T cell activation. A biological function emerged from the phenotype of SATB1 knockout mice, where SATB1 was found essential for orchestrating the spatial and temporal expression of a large number of T cell-and stage-specific genes: in the absence of SATB1, T cell development was severely impaired, and immature CD3-/CD4-/CD8-triple negative thymocytes were largely reduced in number.…”
Section: Satb1mentioning
confidence: 99%
“…For ChIP-loop assay, we performed chromatin immunoprecipitation before intramolecular ligation to identify the chromatin loop defined by specific protein. (c) The genomic DNA prepared for either ChIP-loop or 3C assay as described above was subjected to PCR amplification using various combination of forward and reverse primer pairs derived from the DNA fragments (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). These PCR products derived from the 200kb cytokine locus using genomic DNA is designated Th2.…”
Section: Acknowledgementmentioning
confidence: 99%
“…Furthermore, T cell development is arrested mainly at CD4 + /CD8 + (double-positive) stage 15 . SATB1 and its homolog SATB2 are expressed in multiple, but restricted cell types [20][21][22][23][24] , and some important post-translational modifications have been characterized for these proteins 25,26 .…”
Section: Introductionmentioning
confidence: 99%